Practitioner perspectives from seven health professional groups on core competencies in the context of chronic care. Issue 6 (November 2014) - Fouche, Christa; Kenealy, Timothy; Mace, Jennifer; Shaw, John
Abstract The prevalence of chronic illness is growing worldwide and management is increasingly undertaken by interprofessional teams, yet education is still generally provided in separate professions. The aim of this study was to explore the perspectives of New Zealand healthcare practitioners from seven professional groups involved in chronic care (general practice medicine, nursing, occupational therapy, pharmacy, physiotherapy, social work, and speech language therapy) on the core competencies required of those working in this area. The study was set in the context of the chronic care and shared decision-making (SDM) models. The core competencies for chronic care practitioners proposed by the World Health Organisation were used to shape the research questions. Focus groups with expert clinicians (n = 20) and semi-structured interviews with practitioners (n = 32) were undertaken. Findings indicated a high level of agreement that the core competencies were appropriate and relevant for chronic care practitioners but that many educational and practice gaps existed and interprofessional education in New Zealand was not currently addressing these gaps. Among the key issues highlighted for attention by educators and policy-makers were the following: teams and teamwork, professional roles and responsibilities, interprofessional communication, cultural competence, better engagement with patients, families, and carers, and common systems, information sharing and confidentiality.